Людина і її буття у західнополіській фразеології - Мацюк, Зоряна Сергіївна (My University, 2016)
Дисертація присвячена дослідженню західнополіської ареальної фразеології. У науковій розвідці здійснено комплексний аналіз ФО у межах опозиції „чоловік” – „жінка”. У результаті ідеографічної класифікації фраземіки Західного Полісся отримано два фразеотематичних поля: «Тілесні ознаки людини в межах опозиції „чоловіче” – „жіноче”» та «Поведінка та внутрішній світ людини в межах опозиції „чоловіче – „жіноче”», які поділено на фразеосемантичні групи („Загальний зовнішній вигляд”, „Частини тіла чоловіків / жінок”, „Специфічні жіночі ознаки”, „Поведінкові риси”, „Мовлення”, „Ставлення до праці”, „Внутрішній світ”, „Інтелект людини” тощо). Кожну фразеосемантичну групу поділено на фразеосемантичні ряди. Гендерний підхід аналізу західнополіської фразеології дав можливість диференціювати сполуки на такі групи: фраземи із власне маскулінними ознаками; фраземи із власне фемінними ознаками; маскулінні фраземи, умотивовані лексико-граматичною категорійністю; фемінні фраземи, умотивовані лексико-граматичною категорійністю; фраземи з невмотивованою лексико-граматичною категорійністю; гендерно марковані фраземи з лексичними номінативними чоловічими та жіночими компонентами; гендерно антропонімні фраземи; ФО без виразних гендерних ознак.

The thesis is devoted to the research of Western Polessian local phraseology. Complex analysis of the phraseological unit within the opposition „male” – „female” has been fulfilled. As a result of the ideographic classification two phraseological thematic fields have been distinguished: «Corporal Features of a Human Being within the Opposition „Male” – „Female”» and «Behaviour and Inner World of a Person within the Opposition „Male” – „Female”». These two fields have been divided into 13 phraseological semantic groups („General Appearance”, „Males’/Females’ Parts of Body”, „Special Females’ Features”, „Behavioural Features”, „Speech”, „Attitude to Work”, „Usage of Alcohol”, „Inner World”, „Psycho-emotional State”, „Volitional Features”, „Human Intelligence”, „Sleep”, „Opposition of Life and Death”). Every phraseological semantic group is divided into phraseological semantic categories. It is worth mentioning that some phaseological units are referred to several phraseological semantic categories as they can have similar and opposite meanings. Their meanings vary among residents of different areas. In contrast to taking a traditional approach to the analysis of the Western Polessian phraseology, use of a gender-based perspective makes it possible to differentiate the combinations into such groups: phraseological units with strictly masculine features, phraseological units with strictly feminine features, masculine phraseological units which are motivated by lexical and grammatical categories, feminine phraseological units which are motivated by lexical and grammatical categories, phraseological units which are not motivated by lexical and grammatical categories, gender phraseological units with lexical nominative male and female components, gender antroponymic phraseological units, and common phraseological units. Gender phraseologic units are an integral part of the phraseological system of Western Polessia. A wide range of phraseological units can be included into one phraseological field, as they can have various forms and be polysemantic.
Keywords: фразеотематичне поле; фразеосемантична група; фразема; ідеографічний опис; ареальна фразеологія; опозиція; гендер; маскулінність; фемінність; мовні маркери; phraseological thematic field; phraseological semantic group; phraseological unit; phraseological semantic row; ideographic description; local phraseology; opposition; gender; masculine; feminine; language markers